Role of Chromosome Changes in Evolution and Diversity - Kornsorn Srikulnath; Watcharaporn Thapana; Narongrit Muangmai (Genomics & Informatics)
The karyotypes of most species of crocodilians were studied using conventional and molecular cytogenetics. These provided an important contribution of chromosomal rearrangements for the evolutionary processes of Crocodylia and Sauropsida (birds and reptiles). The karyotypic features of crocodilians contain small diploid chromosome numbers (30~42), with little interspecific variation of the chromosome arm number (fundamental number) among crocodiles (56~60). This suggested that centric fusion and/or fission events occurred in the lineage, leading to crocodilian evolution and diversity. The chromosome numbers of Alligator, Caiman, Melanosuchus, Paleosuchus, Gavialis, Tomistoma, Mecistops, and Osteolaemus were stable within each genus, whereas those of Crocodylus (crocodylians) varied within the taxa. This agreed with molecular phylogeny that suggested a highly recent radiation of Crocodylus species. Karyotype analysis also suggests the direction of molecular phylogenetic placement among Crocodylus species and their migration from the Indo-Pacific to Africa and The New World. Crocodylus species originated from an ancestor in the Indo-Pacific around 9~16 million years ago (MYA) in the mid-Miocene, with a rapid radiation and dispersion into Africa 8~12 MYA. This was followed by a trans-Atlantic dispersion to the New World between 4~8 MYA in the Pliocene. The chromosomes provided a better understanding of crocodilian evolution and diversity, which will be useful for further study of the genome evolution in Crocodylia.